Characterization of Two Novel Toti-Like Viruses Co-infecting the Atlantic Blue Crab, Callinectes sapidus, in Its Northern Range of the United States - Zhao, Mingli; Xu, Lan; Bowers, Holly; Schott, Eric J. (Frontiers in Microbiology, 2022)
The advancement of high throughput sequencing has greatly facilitated the exploration of viruses that infect marine hosts. For example, a number of putative virus genomes belonging to the Totiviridae family have been described in crustacean hosts. However, there has been no characterization of the most recently discovered putative viruses beyond description of their genomes. In this study, two novel dsRNA virus genomes were discovered in the Atlantic blue crab (Callinectes sapidus) and further investigated. Sequencing of both virus genomes revealed that they each encode RNA dependent RNA polymerase proteins (RdRps) with similarities to toti-like viruses. The viruses were tentatively named Callinectes sapidus toti-like virus 1 (CsTLV1) and Callinectes sapidus toti-like virus 2 (CsTLV2). Both genomes have typical elements required for -1 ribosomal frameshifting, which may induce the expression of an encoded ORF1-ORF2 (gag-pol) fusion protein. Phylogenetic analyses of CsTLV1 and CsTLV2 RdRp amino acid sequences suggested that they are members of two new genera in the family Totiviridae. The CsTLV1 and CsTLV2 genomes were detected in muscle, gill and hepatopancreas of blue crabs by real-time reverse transcription quantitative polymerase chain reaction (RT-qPCR). The presence of ~40 nm totivirus-like viral particles in all three tissues was verified by transmission electron microscopy, and pathology associated with CsTLV1 and CsTLV2 infections were observed by histology. PCR assays showed the prevalence and geographic range of these viruses to be restricted to the northeast US sites sampled. The two virus genomes co-occurred in almost all cases, with the CsTLV2 genome being found on its own in 8.5% cases, and the CsTLV1 genome not yet found on its own. To our knowledge, this is the first report of toti-like viruses in C. sapidus. The information reported here provides the knowledge and tools to investigate transmission and potential pathogenicity of these viruses.